Article publication for law subjects: overview and experiences - Zulhuda, Sonny (2020)
The objective of this presentation was to share on trends, challenges and tips of publications for legal academia. The contents include Overview, Some Basic Rules of Academic Writing, Common Mistakes, and the Reviewers’ Guideline Samples. The author shares his experience being a member of some law journal editors, including IIUM Law Journal and Pertanika (as special editor).